Analysis of dissipated energy and temperature fields at severe notches of AISI 304L stainless steel specimens (Fracture and Structural Integrity, 2018)
In the last years, a large amount of fatigue test results from plain and bluntly notched specimens made of AISI 304L stainless steel were synthetized in a single scatter band by adopting the specific heat loss per cycle (Q) as a damage parameter. During a fatigue test, the Q parameter can be evaluated measuring the cooling gradient at a point of the specimens after having suddenly stopped the fatigue test. This measurement can be done by using thermocouples; however, due to the high stress concentration at the tip of severely notched components analysed in the present paper, an infrared camera achieving a much improved spatial resolution was adopted. A data processing technique is presented to investigate the heat energy distribution close to the notch tip of hot-rolled AISI 304L stainless steel specimens, having notch tip radii equal to 3, 1 and 0.5 mm and subjected to constant amplitude cyclic loads. A thermal finite element analysis was also performed by assigning heat generation in the appropriate region close to the notch tip. Then the numerical temperature values were compared with the experimental measurement.
Keywords: Energy Distribution; Fatigue; Notch Effect